Silver (I) N-Heterocyclic Carbenes Carbosilane Dendritic Systems and Their Imidazolium-Terminated Analogues as Antibacterial Agents: Study of Their Mode of Action - Rodríguez-Prieto, Tamara (Pharmaceutics, 2020)
Spherical dendrimers and dendrons containing silver(I) N-heterocyclic carbenes (Ag(I)-NHC) and additionally bow-tie metal-free dendritic systems were synthesized in a simple and straightforward synthetic procedure and subsequently characterized. The antibacterial activity was evaluated, and in parallel, a comparative study with the cationic analogue precursors was performed to explore the effect of silver ions in the dendritic structure. Other parameters, such as topology, generation, and hydrophobicity, of the imidazole substituents were also studied. All these dendritic systems presented antibacterial activity against three different bacterial strains, two Gram-positive (Staphylococcus aureus and Bacillus subtilis) and one Gram-negative (Escherichia coli). Several assays were conducted to elucidate their mechanism of action against Bacillus subtilis, by using bacterial biosensors or specific probes and fluorescent proteins sensitive to changes in the cell membrane potential. These studies are specially focused on the role of the polyvalence of our systems containing silver atoms, which may provoke interesting effects in the mode of action.